Interventions for cognitive frailty: developing a Delphi consensus with multidisciplinary and multisectoral experts - Holland, Carol A.; Dravecz, Nikolett; Broughton, Susan; Barker, Lynne A.; Bature, Fidelia; Clarke, Charlotte; Danat, Isaac M.; Das, Sayani; Dias, Irundika H. K.; Dawson, Annabel; Dixon, M.; Ellison, Amanda; et al. (Frontiers in Aging Neuroscience, 2025)
IntroductionThe conjunction of physical frailty and cognitive impairment without dementia is described as Cognitive Frailty (CF). Indications that CF is potentially reversible have led to proposals that risk factors, symptoms or mechanisms of CF would be appropriate targets for interventions for prevention, delay or reversal. However, no study has brought experts together across sectors to determine targets, content or mode of interventions, and most resources on interventions are from the perspective of academic or clinical researchers only. This international Delphi consensus study brings together experts from academic and clinical research, lay people with lived experience of CF, informal carers, and professional care practitioners/clinicians.MethodsThree rounds of Delphi study were held to discern which factors and statements were agreed upon by the whole sample and which generated different views in those with differing expertise. A scoping review and Round 1 (29 participants) were used to gather initial statements. In Round 2, 58 people responded to statements and open text items, comprising 7 lab-based researchers, 27 researchers working with people, 14 people with lived experience or informal family carers, and 10 professional carers/clinicians. Percent agreement and qualitative responses were analyzed to provide a final set of statements which were checked by 38 respondents in Round 3.ResultsAnalysis of Round 2 quantitative data provided 74 statements on which there was at least 70% agreement and qualitative data produced a further 24 statements. These were combined to provide 90 statements for Round 3. There was Consensus for 89 of the statements. A few differences between the groups were observed at both stages.Discussion and conclusionThe consensus for statements associated with CF interventions provides a useful first step in defining health promotion activities and interventions. Given the prevalence and potential disability caused by CF in older populations, the consensus statements represent expert opinion that is inter-sectoral and will inform public health policies to support implementation of evidence-based prevention and intervention plans. This study is an important step toward changing current approaches, by including all stakeholders from the outset. Outcomes can be used to feed into co-creation of interventions for cognitive frailty.